Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2008
DOI: 10.1002/jmv.21285
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterization of genotype 2 and 4 hepatitis C virus isolates in French blood donors

Abstract: The subtype distribution of 142 genotype 2 and 97 genotype 4 hepatitis C virus (HCV) isolates from the sera of 1,319 volunteer blood donors in France was determined by gene sequencing and by phylogenetic analysis of the NS5B region and E1 envelope. Findings underlined a wide range of subtypes in both genotypes, that is, 20 in HCV-2 and 11 in HCV-4. Eighteen of these 31 subtypes had not been defined previously. Some subtypes, that is, 2a, 2b, 2c, 2i, 2k, 4a, and 4d, showed numerous strains while subtypes in don… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
28
0
2

Year Published

2008
2008
2015
2015

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(34 citation statements)
references
References 54 publications
4
28
0
2
Order By: Relevance
“…During the 20th century, transmission via contaminated blood, blood products, invasive procedures, and IDU eventually resulted in the global dispersal of HCV-2, particularly subtypes 2a and 2b, which cause the vast majority of HCV-2 infections in developed countries (9,11,44). Interestingly, two recent studies from France revealed a wide variety of HCV-2 subtypes, including among the native French population (5,40).…”
mentioning
confidence: 99%
“…During the 20th century, transmission via contaminated blood, blood products, invasive procedures, and IDU eventually resulted in the global dispersal of HCV-2, particularly subtypes 2a and 2b, which cause the vast majority of HCV-2 infections in developed countries (9,11,44). Interestingly, two recent studies from France revealed a wide variety of HCV-2 subtypes, including among the native French population (5,40).…”
mentioning
confidence: 99%
“…The MRCAs of HCV-4 in CAR and Cameroon are much older than that of the genotype 4 strains found in Europe (MRCA, approx. 1900) (Cantaloube et al, 2008) and Egypt (MRCA existed approx. 100 years ago) (Pybus et al, 2003;Tanaka et al, 2004), reinforcing our previous suggestion that HCV-4 originated in central Africa, diverged and then spread to the rest of the world.…”
mentioning
confidence: 99%
“…4 Modeling suggests that HCV genotype 4 could play an important role in the future HCV burden in industrialized countries. 5 Further studies are warranted to assess the frequency of undetected HCV RNA with the CAP-CTM assay. Improvement in this assay is now urgently needed in order to ensure accurate quantification of HCV RNA, regardless of the HCV genotype, for optimal use in clinical trials and practice.…”
mentioning
confidence: 99%